Mutations in LONP1, a mitochondrial matrix protease, cause CODAS syndrome - Dikoglu, Esra; Alfaiz, Ali; Gorna, Maria; Bertola, Deborah; Chae, Jong Hee; Cho, Tae-Joon; Derbent, Murat; Alanay, Yasemin; Guran, Tulay; Kim, Ok-Hwa; Llerenar Jr, Juan C.; Yamamoto, Guillerme; et al. (American journal of medical genetics. Part A, 2015)
Cerebral, ocular, dental, auricular, skeletal anomalies (CODAS) syndrome (MIM 600373) was first described and named by Shehib et al, in 1991 in a single patient. The anomalies referred to in the acronym are as follows: cerebral‐developmental delay, ocular‐cataracts, dental‐aberrant cusp morphology and delayed eruption, auricular‐malformations of the external ear, and skeletal‐spondyloepiphyseal dysplasia. This distinctive constellation of anatomical findings should allow easy recognition but despite this only four apparently sporadic patients have been reported in the last 20 years indicating that the full phenotype is indeed very rare with perhaps milder or a typical presentations that are allelic but without sufficient phenotypic resemblance to permit clinical diagnosis. We performed exome sequencing in three patients (an isolated case and a brother and sister sib pair) with classical features of CODAS. Sanger sequencing was used to confirm results as well as for mutation discovery in a further four unrelated patients ascertained via their skeletal features. Compound heterozygous or homozygous mutations in LONP1 were found in all (8 separate mutations; 6 missense, 1 nonsense, 1 small in‐frame deletion) thus establishing the genetic basis of CODAS and the pattern of inheritance (autosomal recessive). LONP1 encodes an enzyme of bacterial ancestry that participates in protein turnover within the mitochondrial matrix. The mutations cluster at the ATP‐binding and proteolytic domains of the enzyme. Biallelic inheritance and clustering of mutations confirm dysfunction of LONP1 activity as the molecular basis of CODAS but the pathogenesis remains to be explored. © 2015 Wiley Periodicals, Inc.